Nutrition and physical activity in infants and breastfeeding women 2024: Partly updated recommendations by “Healthy Start Network” (Netzwerk Gesund ins Leben) Ernährung und Bewegung von Säuglingen und stillenden Frauen 2024: Teilaktualisierte Handlungsempfehlungen des bundesweiten Netzwerks Gesund ins Leben - Abou-Dakn, Michael; Abu-Omar, Karim; Alaze-Hagemann, Felizitas; Alexy, Ute; Bauer, Carl Peter; Beyer, Kirsten; Cierpka, Manfred; Cremer, Monika; Ensenauer, Regina; Fast, Marischa; Flothkötter, Maria; Heindl, Ines; et al. (Monatsschrift Kinderheilkunde, 2024)
Background: During the first year after the birth of a child, nutrition and physical activity are particularly important for the short and long-term health of both mother and child. The recommendations for action on nutrition and physical activity in infants and breastfeeding women are now partially updated and are intended to provide health professionals with a reliable basis for advising families with infants. Method: Based on recommendations from relevant specialist organizations and institutions as well as systematic reviews, meta-analyses, guidelines and other reliable study data, the scientific advisory board of the Healthy Start Network and other experts assessed the scientific evidence and formulated recommendations for action. A partial update took place in 2024. This concerns the recommendations for selecting infant formula when there is an increased risk of allergies, and for fluoride in the first year of life. All other recommendations reflect the status of 2016. Both processes were coordinated by the Healthy Start Network. Recommendations: The recommendations for action cover the topics of breastfeeding, infant formula, complementary food, beverages or supplementary fluid intake, learning to eat, diet of breastfeeding women, nutritional supplements for infants and breastfeeding women as well as alcohol, smoking and medication during the lactation period. It also contains general recommendations on allergy prevention in children as well as recommendations on physical activity in infancy and for breastfeeding women.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Allergy prevention; Breastfeeding; Complementary food; Infant formula; Physical activity